2019
DOI: 10.1111/pedi.12852
|View full text |Cite
|
Sign up to set email alerts
|

Novel, culturally sensitive, shared medical appointment model for Hispanic pediatric type 1 diabetes patients

Abstract: Background/Objective Latino patients with type 1 diabetes (T1D) face cultural and language barriers leading to poor outcomes. Shared medical appointments (SMAs) are recognized as effective models of care. Our aim is to develop a culturally sensitive, cost effective SMA program for Latino T1D. Subjects Spanish speaking Latinos 1 to 20 years with T1D (n = 88) and their families. Methods Routine care alternating with SMAs that included group education was provided. Teens, ages >11 received the SMA separate from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Additionally, a shared medical appointment clinical model for Hispanic youths and families has been developed and studied. Participation in this clinical model was associated with improvement in glycemic control and an increase in technology use ( 25 ). More interventions similar to these are needed to close the gap in diabetes care between non-Hispanic Whites and individuals of other racial and ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a shared medical appointment clinical model for Hispanic youths and families has been developed and studied. Participation in this clinical model was associated with improvement in glycemic control and an increase in technology use ( 25 ). More interventions similar to these are needed to close the gap in diabetes care between non-Hispanic Whites and individuals of other racial and ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] In adults with T1D or T2D, SMA are associated with improved A1C levels, positive attitudes and outlook, and a sense of empowerment. [18][19][20][21] More recently, studies have examined SMA benefits in the adolescent T1D population, [22][23][24][25][26] finding higher caregiver, patient, and staff satisfaction 25 ; increased peer support 25 ; improved glycemic control 26 ; and adherence. 24 However, investigation into whether SMA improve psychosocial factors in youth and adolescents with T1D has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…among the child participants and increasing diabetes technology use in both children and adolescents, with further benefits in relationshipbuilding between parents and caregivers who shared cultural and language backgrounds. 59 Our study has several unique strengths. There is a lack of literature surrounding the lived experience of Hispanic caregivers of children with T1D.…”
Section: Discussionmentioning
confidence: 96%
“…There are limited trials of group‐based interventions and most take place in adult populations with T2D and/or do not address application to Hispanic cultures 55–58 . One recent study found that shared medical appointments for Hispanic patients were effective in decreasing HbA1c among the child participants and increasing diabetes technology use in both children and adolescents, with further benefits in relationship‐building between parents and caregivers who shared cultural and language backgrounds 59 …”
Section: Discussionmentioning
confidence: 99%